Analisis Evaluasi dan Pengendalian Manajemen Dalam Mengukur Kinerja Perusahaan - Gunawan Aji; Irkhamna Oktavia; Miftakhul Ayu Khoirani; Siti Zulkaidah (Transformasi: Journal of Economics and Business Management, 2023)
A company in achieving its goals needs good strategic management, including through management evaluation and control. However, in Indonesia there are still some problems in the performance implementation process. This study aims to analyze the evaluation and management methods in measuring and controlling company performance. The study has a qualitative descriptive approach with data generated from relevant journals. As for the results of discussions on this study, both evaluation and management control will play a crucial role in measuring corporate performance. With management evaluation and control, company goals can be achieved as planned